Constituer l’archive dont il fallait me débarrasser - Sylvie Kandé; Violaine François (Continents manuscrits, 2024)
Through evoking the poet-president in her personal and poetic journey, Sylvie Kandé explores various aspects of her writing. This includes her relationship with literary sources, ranging from found poetry to unconscious inspiration. Her writing seeks to push the boundaries of language and time, drawing from diverse registers and presenting new lexical discoveries. For Kandé, writing also entails “delving into the accumulations and complexities of every condition”, whether it pertains to migrants across centuries and continents, or to women whose human and mythological figures are portrayed in their diversity. By generously sharing a few pages from her red notebook, Sylvie Kandé unveils the intricate process of her writing and invites readers into her world, where the texts of Senghor resonate like a distant echo.